Local Man on Cali Train - Unknown (Unknown)
Jerry Aspland, a Pacifica High School graduate, was one of 87 Merchant Marine cadets aboard a passenger train in Cali, Colombia, which collided with a locomotive, killing 29 and injuring 46 yesterday.